GENERAL HEIGHT-DIAMETER EQUATION WITH BIOLOGICAL ATTRIBUTES FOR Pinus taeda L. STANDS - Saulo Jorge Téo (CERNE, 2017)
The aim of this study was to develop an equation with biological attributes and general applicability, to represent the height-diameter relationship for Pinus taeda L. stands, with and without thinning, in the Middle West region of Santa Catarina state, Brazil. The data came from 652 permanent plots, with 428 to 740 m 2 , located in forest stands with ages ranging from 4.6 to 35.2 years, in which the total heights of about 20% of the trees were measured, in addition to the dominant trees. The functions developed by Harrison, Michailoff, Prodan and Stoffels & Van Soest were fitted with their parameters linear function of stand variables, based on the Gauss-Newton algorithm. In general, the Harrison model, fitted with the parameter linear function of age ( t ), site index ( S ), coefficient of variation of the tree diameters in the plot ( CV d ) and basal area of the plot ( G ), showed the best statistical performance to represent the height-diameter relationship, biological consistency and general applicability for stands of Pinus taeda .